KURVA T-X - Wibowo, Barrend Wellyadi; Hutagalung, Soly Deo Gloria (Journal of Renewable Engineering, 2024)
This seismic method practicum meeting is expected that practitioners are able to meet the objectives of knowing the process of forming the T-X curve in refraction seismic. The practicum was held on Monday, December 5, 2022 at the Faculty of Science and Technology, Jambi University. Based on the T-X curve attached to T-X 1, the reverse direct will be inverted from the forward. This value will be searched for an equation to get the result of rock velocity based on forward and reverse waves. Velocity is the level of rock hardness that will determine the speed of a wave in a rock layer. For interpretation, it can be seen from the table of seismic wave propagation velocity in the rock above. Where for V1 of 333.3333 m/s is included in layered weathered rock. For V2 where the speed value is 1000 m/s is unsaturated sand and gravel. For V3 where the velocity value is 1666,67 m/s, it is sand and shale. The interpretation of these rocks actually requires information about the formation where the data was collected.